Mapping cortical brain development, early life exposures and neural correlates of language skills: findings from the FinnBrain Birth Cohort Study - Silver, Eero (fi=Turun yliopisto|en=University of Turku|, 2023)
Human brain starts to develop in utero during the first trimester of pregnancy, and the rapid structural growth continues postnatally during the first years of life. This suggests the early childhood as a critical period for various neurodevelopmental disorders, but also an ideal time point for interventions to have a great positive effect on later neurodevelopment. Recent evidence suggests that many environmental factors and parental health profiles associate with child’s brain development already in the prenatal period. Despite the increasing knowledge about structural brain development collected from magnetic resonance imaging (MRI) studies, there are still significant gaps of knowledge about the structural mechanisms and timing of the brain maturation during the first five years of life. In this thesis, we assess modern segmentation tools and present the semiautomated segmentation protocol that we have applied in the FinnBrain Birth Cohort Study. Second, we study early cortical brain development, and how it associates with changing perinatal factors and environmental variables at five years of age. Third, we review the latest findings of language-related structural MRI studies carried out with children aged from birth to two years. While presenting our segmentation protocol we discovered that with appropriate quality assessments, the FreeSurfer segmentation tool can be reliably used to analyse cortical metrics of T1 -weighted images of the five-year-olds. We found that sex, obstetric variables and maternal perinatal health profile were associated with cortical development in five-year olds. Different environmental variables modulated cortical development in 5-year-olds in comparison with infant MRI studies, carried out with similar analyses. During the first two years of age, the implicated cerebral areas included many established components of the language networks; including frontal and temporal regions. These regions associated with language skills. This thesis confirms that early exposures affect the brain development through the early childhood, and that we have created segmentation protocol that can be implemented with the structural MRI data. Language development is associated with school performance, and this thesis lays foundations to the future studies, that will continue during the school age also in the FinnBrain Birth Cohort Study.

Varhaiset altisteet, lapsen rakenteellinen aivojen kehitys ja kielelliset taidot: kuvantamistutkimus FinnBrain syntymäkohorttitutkimuksessa Ihmisaivot alkavat kehittyä kohdussa jo äidin ensimmäisen raskauskolmanneksen aikana, ja aivojen rakenteellinen kehitys jatkuu vauhdikkaana syntymän jälkeen ensimmäisen kahden vuoden ajan. Varhaislapsuus on siten keskeinen ajanjakso neurokognitiivisten häiriöiden synnylle, ja siten myös myöhempää neurokognitiivista kehitystä tukevien hoitomuotojen tarjoamiselle. Lisäksi monet ympäristötekijät ja vanhempien hyvinvointi vaikuttavat lapsen aivojen kehitykseen jo ennen syntymää. Vaikka magneettikuvantamistutkimusten ansiosta tiedämme aivojen varhaisvaiheen rakenteellisesta kehityksestä jo suhteellisen paljon, on tietämys aivojen kehityksestä erityisesti viiden ensimmäisen ikävuoden ajalta vielä pitkälti puutteellista. Tutkimustyömme on osa FinnBrain syntymäkohorttitutkimusta. Arvioimme yleisesti käytössä olevia aivojen segmentaatiotyökaluja ja esittelemme laadunvarmistusprotokollan, jonka mukaan olemme käsitelleet keräämämme 5-vuotiaiden magneettikuvantamisaineiston. Toiseksi tutkimme, kuinka raskausajan muuttuvat olosuhteet sekä varhaisiän ympäristötekijät vaikuttavat aivojen rakenteelliseen kortikaaliseen kehitykseen viiden vuoden iässä. Kolmannen osatyön systemaattisessa katsausartikkelissa keräämme yhteen tuoreimmat tulokset kielen kehitystä tarkastelevista kuvantamistutkimuksista ensimmäisen kahden ikävuoden ajalta. Asianmukaisella laaduntarkkailulla FreeSurfer-segmentaatiotyökalu soveltuu 5-vuotiaiden magneettikuvantamisaineiston käsittelyyn hyvin. Toiseksi havaitsimme, että sukupuolella, äidin terveydellä sekä synnytykseen liittyvillä muuttujilla havaittiin yhteyksiä aivojen kortikaalirakenteiden kehitykseen 5-vuotiailla. Aikuisilla havaitut perinteisesti kielellisistä toiminnoista vastaavat aivoalueet, kuten ohimo- ja otsalohkon alueet, olivat havaittavissa ja yhdistettävissä kielellisiin taitoihin jo alle kahden vuoden iässä. Tämä väitöskirja vahvistaa, että varhaiset altisteet vaikuttavat aivojen kehitykseen yli varhaislapsuuden sekä sen, että olemme luoneet rakenteellisen MRI-aineistoon soveltuvat käytänteet. Kielenkehitys liittyy muun muassa koulumenestykseen ja väitöskirja luo vahvan pohjan tulevalle tutkimukselle, joka tulee jatkumaan kouluiässä FinnBrain-tutkimuksessa.